Structure of sea ice in McMurdo Sound, Antarctica - Stephen J. Jones; Brian T. Hill (Annals of Glaciology, 2001)
AbstractSea-ice cores from 11 sites in McMurdo Sound, Antarctica, were collected in 1982 and their crystallography examined. All but one were first-year sea ice. The cores, approximately 2 m long, consisted typically of a thin layer of granular or snow ice (approximately 0.1 m) followed by columnar-grained ice in the top metre and platelet ice in the bottom metre. Salinity and temperature measurements are reported. The columnar-grained ice usually had a strong preferred c-axis orientation in the horizontal plane and also showed a change in this preferred direction with depth in the ice. The mean c-axis orientation, however, usually aligned well with measured or implied currents in the Sound. The platelets were usually aligned with c axis horizontal or close to horizontal, and did not exhibit as marked a preferred orientation as the columnar-grained ice.